Fabrication of MoS2 thin films on oxide‐dielectric‐covered substrates by chemical solution process. Issue 2 (15th November 2016) - Kim, Joonam; Higashimine, Koichi; Haga, Ken‐ichi; Tokumitsu, Eisuke
Abstract : The chemical solution process of MoS2 on high‐ k oxide films has been systematically investigated. The source solution used in this work is made of (NH4 )2 MoS4 powder dissolved in N‐methyl‐2‐pyrrolidone. We have spin‐coated the solution on various kinds of dielectric oxide films and shown that the coating properties strongly depend on the kind of dielectric, which can be understood by surface energy analysis, following this, the growth of high quality of MoS2 film is confirmed by Raman scattering spectroscopy and X‐ray diffraction. It is demonstrated that the MoS2 film can be grown on Nb doped ZrO2 using a solution with a two‐step annealing process, where the first annealing is performed at 450 °C in H2 /Ar (5:95) atmosphere for 20 min and the second annealing at 1000 °C in Ar atmosphere with S vapor for 20 min. In addition, conformal growth of a MoS2 layered structure on the curved surface of the oxide film is confirmed by transmission electron microscope observations. A further conclusion is that the thickness of MoS2 can be controlled by the concentration of a source solution and that two‐layer MoS2 is obtained when the concentration of source solution is 0.00625 mol kg −1 . The measured Hall mobility of the solution‐derived MoS2 film, annealed at 1000 °C is approximately 25 cm 2 V −1 s −1 .